Retracted: "CITRX thioredoxin interacts with the tomato Cf‐9 resistance protein and negatively regulates defence". (17th June 2019) - Rivas, Susana; Rougon‐Cardoso, Alejandra; Smoker, Matthew; Schauser, Leif; Yoshioka, Hirofumi; Jones, Jonathan DG
Abstract : The authors regret to announce they would like to withdraw this paper, for two main reasons: Since the paper was published, it has become clear that the thioredoxin that interacts in yeast 2‐hybrid with the Cf‐9 C‐terminus is in fact localized in the chloroplast, rendering a role in Cf‐9 signalling unlikely. Close scrutiny of the figures suggests several duplications. ‐ In Fig 3A, the Anti‐MBP band in lane 4 closely resembles the antiMBP band in Fig 3B lane 1, though slightly rotated. ‐ In Fig 6A, the leaf disc in the panel labelled TRV:00, −Avr9, 30 min looks identical to the leaf disc in Fig S5, panel labelled Cf2 TRV:CITRX, −Avr2, 1 h. ‐ In Fig 6C, multiple bands appear duplicated. For example, GlucA, TRV:00, −Avr9, 0 h duplicated with 6 h; and GlucB, TRV:00, +Avr9, 0 h duplicated with Hin1, TRV:00, +Avr9, 0 h. Source data for these figures are not available. All the authors agree that this paper should be withdrawn from the scientific literature.